Pengaruh job insecurity dan beban kerja terhadap turnover intention karyawan melalui komitmen afektif sebagai variabel mediasi - Anggraini, Shinta Dwi Nur; Rozaq, Khoirur (Jurnal Ilmu Manajemen, 2025)
This study aims to test and analyze the effect of job insecurity and workload on turnover intention, mediated by affective commitment, among employees of a manufacturing company. This type of research is quantitative research. Sampling using a saturated sampling technique with a total of 92 respondents. Statistical analysis was used in this study using SEM-PLS with the help of SmartPLS 4.1.0.6 software. The results of this study prove that job insecurity has a positive and insignificant effect on turnover intention, workload has a positive and significant impact on turnover intention, job insecurity has a negative and significant effect on affective commitment, workload has a positive and insignificant influence on affective commitment, and affective commitment has a positive and negligible effect on turnover intention. Affective commitment mediation the impact of job insecurity on turnover intention, and affective commitment does not mediate the effect of workload on turnover intention. The study's implications suggest that manufacturing companies should strive to create a safe and conducive work environment and involve employees in all company activities to maintain their commitment and loyalty. In addition, companies also need to pay attention to working hours and tasks assigned to employees to minimize the workload, thereby reducing turnover intention.